Pendekatan Pemecahan Masalah (Problem Solving) dalam Pembelajaran Matematika Kelas Tinggi di SDN Karang Anyar 2 Kota Tangerang - Unaenah, Een; Apriliani, Aira; Afiyah, Azzahra Dhiya; Fitri, Indah Zianira (Lembaga Yasin AlSys, 2023)
Critical thinking is an important skill that must be mastered by students in learning mathematics. An effective problem solving approach for upper grade mathematics learning at SDN Karang Anyar 2 Kota Tangerang is the focus of this research. The exploratory technique used is writing class reviews and perceptions. Information gathering was carried out through a written survey linked to a critical thinking approach in science learning, as well as through direct perception of educational experiences in the elegant environment of SDN Karang Anyar 2. The use of a problem-solving approach in high school mathematics learning at SDN Karang Anyar 2 Kota Tangerang has a number of advantages, including Another is the development of students' creative thinking, critical thinking, and confidence in solving problems. This method also encourages students to develop logical thinking and problem solving skills that can be used in everyday life. In conclusion, the mathematics program for SMA SDN Karang Anyar 2 Kota Tangerang uses a problem solving approach to help students better understand and solve math problems. With this methodology, students are expected to be able to develop critical thinking skills that are useful in their wider life environment.